PELATIHAN PEMBUATAN PAPER SOAP DARI LIMBAH KERTAS DI MADRASAH USWAH AL-ISLAM - Juwairiah Juwairiah; Yusnia Sinambela; Nurianti Sitorus (Universitas Mataram, 2022)
Paper soap itself is one of the innovations of soap products that are thin like paper, this paper soap will dissolve when exposed to water and rubbed on the hands will produce foam. Paper soap is generally used as disposable hand soap because of its small and thin size, making it easy to carry anywhere and suitable for use when doing activities outside the home. To foster creativity on how to recycle used paper into paper soap as a practical solution to bring soap to maintain hand hygiene when you have to do activities outside the home. The method of providing material with lecture and question and answer methods, pre and post tests and the practice of making paper soap from paper waste, consisting of 25 madrasah children in Uswah Al-Islam, especially the MDTA class. This activity resulted in students' creativity in the form of soap made from waste paper, and then the students were given questions in the form of essays with the average results of the pre-test and post-test scores of 25 children being 60.72 and 84.96, it can be seen that post test results increased after being given training in making paper soap. This training can provide the ability and foster creativity of students to make paper soap from paper waste that can be used to maintain hand hygiene.